2013
DOI: 10.1111/jan.12092
|View full text |Cite
|
Sign up to set email alerts
|

RAMESES publication standards: meta‐narrative reviews

Abstract: Background: Meta-narrative review is one of an emerging menu of new approaches to qualitative and mixedmethod systematic review. A meta-narrative review seeks to illuminate a heterogeneous topic area by highlighting the contrasting and complementary ways in which researchers have studied the same or a similar topic. No previous publication standards exist for the reporting of meta-narrative reviews. This publication standard was developed as part of the RAMESES (Realist And MEta-narrative Evidence Syntheses: E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
211
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(233 citation statements)
references
References 20 publications
(62 reference statements)
0
211
0
2
Order By: Relevance
“…This includes selecting search terms and appropriate databases, and deciding on criteria for the inclusion and exclusion of literature. This is important as, independent of the type of approach, the quality of the literature is dependent on, among other aspects, what literature is included and how it was selected (Tranfield, Denyer, and Smart 2003;Wong et al 2013;Liberati et al 2009;Torraco 2005). Thus, the authors must be transparent in a way that enables the reader to understand how the literature was identified, analyzed, synthesized, and reported.…”
Section: The Process Of Conducting a Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…This includes selecting search terms and appropriate databases, and deciding on criteria for the inclusion and exclusion of literature. This is important as, independent of the type of approach, the quality of the literature is dependent on, among other aspects, what literature is included and how it was selected (Tranfield, Denyer, and Smart 2003;Wong et al 2013;Liberati et al 2009;Torraco 2005). Thus, the authors must be transparent in a way that enables the reader to understand how the literature was identified, analyzed, synthesized, and reported.…”
Section: The Process Of Conducting a Literature Reviewmentioning
confidence: 99%
“…There are a number of standards and guidelines that explicitly address how literature reviews should be reported and structured. For example, PRISMA, developed for systematic literature reviews and meta-analyses (see Liberati et al 2009); RAMSES, developed for systematic narrative reviews (see Wong et al 2013); and guidelines for integrative reviews (see Torraco 2005). However, some generalizations can be made.…”
Section: Phase 3: Analysismentioning
confidence: 99%
See 3 more Smart Citations